Linear quantum optics: components and applications - Clements, W (2018)
Quantum optics has successfully been used to test fundamental principles in quantum physics and to demonstrate the potential of quantum-enhanced technologies. Linear quantum optics, in which large quantum states of light are produced by optical interference of smaller quantum states, has proved to be particularly fruitful. Further progress will rely both on developing improved experimental tools to manipulate and measure quantum light, and on expanding and refining the range of applications of these technologies. This thesis presents our contributions towards both of these endeavours. We first focus on some of the components necessary for linear quantum optics, starting with the requirement for reconfigurable interference between several optical modes. We propose a novel design for interferometers that satisfy this requirement, which is based on a new mathematical decomposition of unitary matrices used to describe optical interference. We show that our design is more efficient than previously known designs. We also experimentally demonstrate a modular approach to building these devices, which is based on the assembly of multiple UV-written integrated photonic chips. These chips are characterised, and three of them are assembled into a structure shown to enable a wide range of optical transformations. We then study methods of photon detection, showing how photon detectors can be calibrated and discussing the operation of superconducting photon number resolving transition edge sensors. Next, we study two applications of linear optics. We examine the applicability of a proposal for simulating molecular spectroscopy using quantum optics in the presence of experimental imperfections. Our findings are illustrated with a proof of principle experiment in which we simulate part of the vibronic spectrum of the tropolone molecule. Finally, we study a class of optical devices, known as optical Ising machines, that has been shown to find solutions to difficult combinatorial problems. Describing the optical pulses in these devices in phase space as Gaussian quasi-probability distributions that evolve stochastically, we analyse the computational mechanism of these machines and show in theory that they can be simplified without affecting their performance.